Drawing: the bottom line - Cauteren, Philippe van 1969-; Germann, Martin 1974- (Mercatorfonds, 2015)
"Presents the works of fifty-three artists from around the globe, all working within the medium of drawing and exploiting its versatile nature in a wide variety of ways. From brief sketches to fully realized and complex constructions, drawing provides the preliminary foundation for all of these works, whether they are simply functional process materials or products of careful consideration. This extensive survey features works from a wide range of prominent contemporary art figures, including Francis Alÿs, Paul McCarthy, Tacita Dean, Roni Horn, Gabriel Orozco, Raymond Pettibon, and many others, as well as written contributions and short introductory texts from dozens of renowned critical voices, many of which have been selected by the artists themselves. Furthermore, the volume contains an essay by influential British writer John Berger. While drawing is often thought of as an incomplete or loosely defined form, this unique anthology and the varying practices of its participants help to demonstrate drawing's extraordinarily distinctive properties and nearly infinite possibilities, affirming its significance as an artistic language"--Back cover